ABO blood group and COVID‐19: a review on behalf of the ISBT COVID‐19 Working Group. Issue 8 (12th February 2021) - Goel, Ruchika; Bloch, Evan M.; Pirenne, France; Al‐Riyami, Arwa Z.; Crowe, Elizabeth; Dau, Laetitia; Land, Kevin; Townsend, Mary; Jecko, Thachil; Rahimi‐Levene, Naomi; Patidar, Gopal; Josephson, Cassandra D.; et al.
Abstract: Growing evidence suggests that ABO blood group may play a role in the immunopathogenesis of SARS‐CoV‐2 infection, with group O individuals less likely to test positive and group A conferring a higher susceptibility to infection and propensity to severe disease. The level of evidence supporting an association between ABO type and SARS‐CoV‐2/COVID‐19 ranges from small observational studies, to genome‐wide‐association‐analyses and country‐level meta‐regression analyses. ABO blood group antigens are oligosaccharides expressed on red cells and other tissues (notably endothelium). There are several hypotheses to explain the differences in SARS‐CoV‐2 infection by ABO type. For example, anti‐A and/or anti‐B antibodies (e.g. present in group O individuals) could bind to corresponding antigens on the viral envelope and contribute to viral neutralization, thereby preventing target cell infection. The SARS‐CoV‐2 virus and SARS‐CoV spike (S) proteins may be bound by anti‐A isoagglutinins (e.g. present in group O and group B individuals), which may block interactions between virus and angiotensin‐converting‐enzyme‐2‐receptor, thereby preventing entry into lung epithelial cells. ABO type‐associated variations in angiotensin‐converting enzyme‐1 activity and levels of von Willebrand factor (VWF) and factor VIII could also influence adverse outcomes, notably in group A individuals who express high VWF levels. In conclusion, group O may be associated with a lower risk of SARS‐CoV‐2 infection and group A may be associated with a higher risk of SARS‐CoV‐2 infection along with severe disease. However, prospective and mechanistic studies are needed to verify several of the proposed associations. Based on the strength of available studies, there are insufficient data for guiding policy in this regard.